Identification of the Nitrogen Interstitial as Origin of the 3.1 eV Photoluminescence Band in Hexagonal Boron Nitride. Issue 7 (6th May 2021) - Khorasani, Elham; Frauenheim, Thomas; Aradi, Bálint; Deák, Peter
Abstract : Nitrogen interstitials ( N i ) have the lowest formation energy among intrinsic defects of hexagonal boron nitride (hBN) under n‐type and N‐rich conditions. Using an optimized hybrid functional, which reproduces the gap and satisfies the generalized Koopman's condition, an N i configuration is found, which is lower in energy than the ones reported so far. The (0/–) charge transition level is also much deeper, so N i acts as a very efficient compensating center in n‐type samples. Its calculated photoluminescence (PL) at 3.0 eV agrees well with the position of an N‐sensitive band measured at 3.1 eV. It is also found that the nitrogen vacancy ( V N ) cannot be the origin of the three‐boron‐center (TBC) electron paramagnetic resonance (EPR) center and in thermal equilibrium it is even unlikely to exist in n‐type samples. Abstract : The nitrogen interstitial N i is identified as the origin of the N‐related photoluminescence band at 3.1 eV in hexagonal boron nitride. In n‐type samples, N i is energetically preferred over the nitrogen vacancy V N even in extremely N‐poor samples. In addition, V N is excluded as the origin of the so‐called three‐boron‐center electron paramagnetic resonance in carbon‐poor, irradiated samples.